One and a half million hematopoietic stem cell transplants: continuous and differential improvement in worldwide access with the use of non-identical family donors - Niederwieser, Dietger; Baldomero, Helen; Bazuaye, Nosa; Bupp, Caitrin; Chaudhri, Naeem; Corbacioglu, Selim; Elhaddad, Alaa; Frutos, Cristóbal; Galeano, Sebastian; Hamad, Nada; Hamidieh, Amir Ali; Hashmi, Shahrukh; et al. (Haematologica (Roma), 2022)
The Worldwide Network of Blood and Marrow Transplantation (WBMT) pursues the mission of promoting hematopoietic cell transplantation (HCT) for instance by evaluating activities through member societies, national registries and individual centers. In 2016, 82,718 first HCT were reported by 1,662 HCT teams in 86 of the 195 World Health Organization member states representing a global increase of 6.2% in autologous HCT and 7.0% in allogeneic HCT and bringing the total to 1,298,897 procedures. Assuming a frequency of 84,000/year, 1.5 million HCT were performed by 2019 since 1957. Slightly more autologous (53.5%) than allogeneic and more related (53.6%) than unrelated HCT were reported. A remarkable increase was noted in haploidentical related HCT for leukemias and lymphoproliferative diseases, but even more in non-malignant diseases. Transplant rates (TR; HCT/10 million population) varied according to region reaching 560.8 in North America, 438.5 in Europe, 76.7 in Latin America, 53.6 in South East Asia/Western Pacific (SEA/WPR) and 27.8 in African/East Mediterranean (AFR/EMR). Interestingly, haploidentical TR amounted to 32% in SEA/WPR and 26% in Latin America, but only 14% in Europe and EMR and 4.9% in North America of all allogeneic HCT. HCT team density (teams/10 million population) was highest in Europe (7.7) followed by North America (6.0), SEA/WPR (1.9), Latin America (1.6) and AFR/EMR (0.4). HCT are increasing steadily worldwide with narrowing gaps between regions and greater increase in allogeneic compared to autologous activity. While related HCT is rising, largely due to increase in haploidentical HCT, unrelated HCT is plateauing and cord blood HCT is in decline.